2019
DOI: 10.1177/1591019919828657
|View full text |Cite
|
Sign up to set email alerts
|

Delayed development of a de novo contralateral middle cerebral artery aneurysm in a patient with hyperimmunoglobulin E syndrome: A case report

Abstract: A 50-year-old female patient with hyperimmunoglobulin E syndrome (HIES) presented initially at the age of 48 years with subarachnoid hemorrhage (SAH) from a ruptured left middle cerebral artery (MCA) bifurcation aneurysm, which was treated successfully with coiling and microsurgical clipping. Angiography and cross-sectional imaging did not indicate evidence of any additional intracranial aneurysm. However, the patient presented two years later with SAH secondary to a new ruptured right MCA bifurcation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The TNF-α-induced STAT3 phosphorylation was prevented by the IL-6R antagonist, indicating that the effect is mediated by an autocrine signaling loop through TNF-α-induced secretion of IL-6 (Supplemental Figure 2A). Indeed, measurement of IL-6 in cell culture medium confirmed that both control and AD-HIES skin fibroblasts increased IL-6 secretion in response patients live long enough for nonimmune complications to become a major cause of death (10,16,17). In the current study, we investigate mechanisms underlying nonimmune abnormalities of AD-HIES in order to better understand the disease pathophysiology and find a promising target or targets for pharmacological therapy.…”
Section: Introductionmentioning
confidence: 87%
“…The TNF-α-induced STAT3 phosphorylation was prevented by the IL-6R antagonist, indicating that the effect is mediated by an autocrine signaling loop through TNF-α-induced secretion of IL-6 (Supplemental Figure 2A). Indeed, measurement of IL-6 in cell culture medium confirmed that both control and AD-HIES skin fibroblasts increased IL-6 secretion in response patients live long enough for nonimmune complications to become a major cause of death (10,16,17). In the current study, we investigate mechanisms underlying nonimmune abnormalities of AD-HIES in order to better understand the disease pathophysiology and find a promising target or targets for pharmacological therapy.…”
Section: Introductionmentioning
confidence: 87%
“…Cerebrovascular aneurysms may be silent or present symptomatically with rupture, causing significant mortality [ 91 ]. Management of asymptomatic aneurysms poses a dilemma, as intervention confers significant risk.…”
Section: Clinical Spectrum Of Stat3-hiesmentioning
confidence: 99%
“…Medium size arterial abnormalities are most common, particularly affecting coronary and intracranial vasculature 95 . Cerebrovascular aneurysms can be silent or present symptomatically with rupture causing significant mortality 96 . The etiology of vasculopathy in HIES is not well understood and how vascular disease may be prevented in this patient population remains unknown.…”
Section: Stat3‐related Diseasementioning
confidence: 99%
“…Optimizing bone health and modifiable risk factors for coronary arterial disease, such as hypertension and hyperlipidemia are also recommended. Patients should undergo surveillance for arterial aneurysms every 3–5 years 96 . The role of HSCT for AD HIES remains uncertain.…”
Section: Stat3‐related Diseasementioning
confidence: 99%
See 1 more Smart Citation